2020
DOI: 10.1177/0885328220948030
|View full text |Cite
|
Sign up to set email alerts
|

Gene-modified BMSCs encapsulated with carboxymethyl cellulose facilitate osteogenesis in vitro and in vivo

Abstract: Critical size bone defects are one of the most serious complications in orthopedics due to the lack of effective osteogenesis treatment. We fabricated carboxymethyl cellulose with phenol moieties (CMC-ph) microcapsules loaded with gene-modified rat bone mesenchymal stem cells (rBMSCs) that secrete hBMP2 following doxycycline (DOX) induction. The results showed that the morphology of microcapsules was spherical, and their diameters have equally distributed in the range of 100–150 μm; the viability of rBMSCs was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Over the Due to the facile, low-cost synthesis process, an abundance of raw materials, characteristic surface properties [24,25], mechanical strength [26], different formability [27,28], tuneable hydrophilicity [29][30][31][32], a viscosity [33], rheological properties [34], and likewise hundreds of other contrasting aspects, CMC and CMC-based hybrid materials have found a wide range of applications in the biomedical, pharmaceutical, textile, construction, food, plastics, cosmetics, paper, and oil industries. For instance, in biomedical fields, CMC and its composites are widely used in tissue engineering [35][36][37][38], bone-tissue engineering [39][40][41], wound dressing [31,32,[42][43][44], absorbent nonwovens [30], fabrication of 3D-scaffolds for biocompatible implants [45,46], artificial organs or mimics of extracellular polymeric matrix [47,48], diagnosis of various diseases [49,50], etc. for various purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Over the Due to the facile, low-cost synthesis process, an abundance of raw materials, characteristic surface properties [24,25], mechanical strength [26], different formability [27,28], tuneable hydrophilicity [29][30][31][32], a viscosity [33], rheological properties [34], and likewise hundreds of other contrasting aspects, CMC and CMC-based hybrid materials have found a wide range of applications in the biomedical, pharmaceutical, textile, construction, food, plastics, cosmetics, paper, and oil industries. For instance, in biomedical fields, CMC and its composites are widely used in tissue engineering [35][36][37][38], bone-tissue engineering [39][40][41], wound dressing [31,32,[42][43][44], absorbent nonwovens [30], fabrication of 3D-scaffolds for biocompatible implants [45,46], artificial organs or mimics of extracellular polymeric matrix [47,48], diagnosis of various diseases [49,50], etc. for various purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Carboxy-methyl cellulose (CMC) is one of substitute materials playing a binding role in bone formation of implanted scaffold [11]. CMC has been applied to improve injectable characters in various scaffold materials including bone substitutes [12].…”
Section: Introductionmentioning
confidence: 99%
“…and it is soluble in water unlike cellulose. Therefore, it is extensively utilized in numerous applications [27,28]. Moreover, CMC has emerged in electrical applications where Basavaraja et al (2012) reported the blending of CMC with PANI to boost its electrical features as a biosensor [29].…”
Section: Introductionmentioning
confidence: 99%